Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 4 - Integration - 4.1 Exercises: 20

Answer

$= -\frac{1}{2x^{6}} + C$

Work Step by Step

$\int (\frac{3}{x^{7}})dx$ $\int (3x^{-7}) dx$ $= \frac{3x^{-6}}{-6} + C$ $= \frac{(3)(\frac{1}{x^{6}})}{-6}+C$ $= \frac{\frac{3}{x^{6}}}{-6}+C$ $= \frac{3}{x^{6}} \times \frac{1}{-6}+ C$ $= - \frac{3}{6x^{6}} + C$ $= -\frac{1}{2x^{6}} + C$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.